Implementasi Chatbot Untuk Laporan Bug / Error Reporting Dengan Natural Languange Processing (Studi Kasus : CV. Solusi Prima) - Hendri Hendri (LPPM STIKOM Dinamika Bangsa, 2021)
Research at CV. Solusi Prima was done to help implement chatbot on bug report, in order to solve some problems in interaction with client. We use some research method such as observation, interview, and library research. From this research's result there are some problem with working system that is client and staff in terms of report bug, make report which is done separately and manually (via whatsapp). This matter make staff become confused between chat to see report bug and for staff to make report bug for their head manager, and for head manager it's cost a lot of time to recap all of his staff's works in patch bug. Especially if their customer and the staff keep report error numerously, can cause older report bugs not being recorded in system, or some report being recorded but not tidy enough, so the staff will get confused to input report bug one by one, because of that we use this chatbot system based on natural language processing method with messenger application (telegram).Aim to make it easier for staff and client in making bug reports, so no need for staff to make report manually without having to lose previously datas, other than that the data that is display base on realtime so whatever report that is display will automatically broadcasted by system to all company's staffs from the results of the testing, system worked is compatible with what we are planning from the start. With the use of chatbot that have been equipped with natural language processing, make user easier to do reporting without moving their hands from keyboard to mouse too often. All the informations in chatbot will be saved and can be used for doing data analythic, so making chatbot easier to use and making it easy for staff and client to report a bug.